Interoperability in IoT infrastructures for enhanced living environments - Gambi, Ennio; Montanini, Laura; Raffaeli, Laura; Spinsante, Susanna; Lambrinos, Lambros (My University, 2017)
The concept of Internet of Things is being applied in several areas and involves a dramatically increasing number of market sectors. There is a large variety of commercial products, and the competition between different vendors often causes incompatibility among the available solutions. Due to the lack of a reference standard, in the highly fragmented arena of Ambient Assisted Living systems and Smart Home environments, the support to interoperability is recognized as a key requirement for the deployment of successful products. This paper provides a state-of-the-art review of IoT adoption in the field of Ambient Assisted Living systems and Smart Home environments, by describing the most widespread solutions and their main key points, with a specific focus on the features designed to support interoperability. This is currently a matter of interest at a European level, as demonstrated, for example, by the inclusion of interoperability among the requirements that project proposals have to fulfill to be eligible for funding through the AAL Joint Platform calls published in the last years.
Keywords: Interoperability; IoT; Open solution; Smart home platform